Seroprevalence of HIV in blood donors at tertiary care center, M.Y.H. Indore, India - Solanki, Priyanka; Yadav, Ashok; Likhar, Khushboo (International Journal of Research in Medical Sciences, 2018)
Background: Transfusion of blood has become an important mode of transmission of infections such as human immunodeficiency virus and hepatitis B to the recipients. Blood transfusion is a boon in medical era if properly screened. The aim of study was to determine the seroprevalence of HIV donors in blood bank at M.Y.H. Indore. Methods: The study was conducted in the blood bank, M.Y.H. Hospital, Indore. Total 115775 donors attending blood bank were included in the study. All the donor samples were screened for detection of antibodies for human immunodeficiency virus by microwell Enzyme Linked Immunosorption Assay (ELISA) method. The seroprevalence of HIV infection among the donors was determined over a period of five years since January 2013 to December 2017. Results: Total 115775 blood donors were recorded. Out of total 115775 blood donors included in the study, replacement donor were 10766 (9.29%) while voluntary donor were 105009 (90.70%). In the duration of five-year study period, total 80 cases (0.06%) were reactive to HIV. Out of total 115775 blood donors included in the study, maximum cases i.e. 22 (0.08%) cases were found to be positive for HIV infection in year 2017. Out of 10766 replacement donors included in the study, 64 cases (0.59%) were reactive to HIV infection. While out of 105009 voluntary donors, 16 cases (0.01%) were found to be reactive to HIV infection. Voluntary donors are more as compared to the replacement donors. Number of HIV positive patients were found to more in replacement donor as compared to the voluntary donors. Conclusions: The seroprevalence of HIV is low in this study and hence it is concluded that the more the number of voluntary donors, the less the number of HIV positive cases. Voluntary donors can be motivated by proper health education and high quality screening programs.